Inovasi Produk dan Kemasan pada Industri Rumahan Kaos di Dusun Mejing Wetan Desa Ambarketawang Kecamatan Gamping Kabupaten Sleman - Safaah Restuning Hayati; Syah Amelia Manggala Putri; Aqidah Asri Suwarsi (UIN Raden Mas Said Surakarta, 2020)
Partners in this service are t-shirt craftsmen in Mejing Wetan Village, Gamping District, Sleman Regency, D.I Yogyakarta. Partners contribute to providing explanations related to conditions and problems faced by Partners, which then the Service Team will provide the right solution. The problem that was found by Partners was that the packaging of the t-shirts was still simple and less attractive. The second problem, innovation in t-shirt design is still lacking and has not included local cultural wisdom and religious elements. The solution offered to Partners is training and assistance in t-shirt product packaging. The second solution is training and developing t-shirt designs based on local cultural wisdom and adding religious elements. Based on the results of the deliberations, the Partners contribute to providing space and time during the mentoring, training, and business monitoring activities. This PKM program provides several real contributions and can be felt by Partners, namely: increasing the quality and innovation of products (t-shirts) in order to have a higher selling power and increase Partner income. The end result of this PKM activity resulted in product innovation in the form of t-shirts with local cultural wisdom designs by incorporating religious elements and packaging innovations made of cardboard in the form of blocks with contemporary designs.